Conceptual Rules of Modular Educational Technology and Its Role In The Educational Process - Muradova Zulfiya Kayumovna (Web of Scientist International Scientific Research Journal, 2025)
In this article, modular educational technology is an innovative pedagogical method designed to effectively organize the learning process of students in the modern education system. The main goal of this method is to facilitate the gradual and gradual assimilation of knowledge by students. Modular education divides the educational process into several modules, each module includes independent study, practice and theoretical knowledge. Modular education is based on its own special conceptual rules, which are aimed at determining the goals and objectives of education, organizing the educational process and taking into account the needs and requirements of each student.